Introduction: democratization in the early twenty-first century - Croissant, Aurel; Merkel, Wolfgang (Democratization, 2004)
Wolfgang Merkel, Social Science Research Center (WZB), Reichpietschufer 50, D-10785, Berlin. Germany, Email: wolfgang.merkelwz-berlin.de
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 26.03.2021